Science and application of high-intensity interval training solutions to the programming puzzle - Buchheit, Martin 1978-; Laursen, Paul 1971- (Human Kinetics, 2019)
The popularity of high-intensity interval training (HIIT), which consists primarily of repeated bursts of high-intensity exercise, continues to soar because its effectiveness and efficiency have been proven in use by both elite athletes and general fitness enthusiasts. Surprisingly, few resources have attempted to explain both the science behind the HIIT movement and its sport-specific application to athlete training. That's why Science and Application of High-Intensity Interval Training is a must-have resource for sport coaches, strength and conditioning professionals, personal trainers, and exercise physiologists, as well as for researchers and sport scientists who study high-intensity interval training. Authors Paul Laursen and Martin Buchheit--both well-known, expert-level HIIT researchers as well as practitioners and endurance athletes--do a masterful job of blending science-based concepts of HIIT with practical application strategies. Laursen, Buchheit, and a team of highly qualified contributors--who bring hundreds of years of combined HIIT science and application experience from across all sports--have written Science and Application of High-Intensity Interval Training to provide practitioners and athletes an understanding of the foundational principles of HIIT programming. Chapters in the first section describe five types of training, how to manipulate HIIT variables to maximize improvements in physical performance, and how to incorporate HIIT into a general training program. Readers will also learn the influence HIIT can have on fatigue, stress, and an athlete's overall health. The final 20 chapters each focus on a different sport and are written by leading coaches or practitioners who have successfully applied HIIT principles at an elite level in their respective sport. These chapters describe specific ways to incorporate HIIT into a training regimen for everything from combat sports to endurance events to the most popular U.S. and international individual and team sports. Each chapter also contains sport-specific preparation and competition phases, an overall one-year training program, and a brief story of how the coach or practitioner who authored the chapter used HIIT to successfully prepare an athlete for a competition. Knowing the proper ways to incorporate high-intensity interval training into a fitness or conditioning program is of vital importance: Not following proper protocols can lead to excessive and prolonged fatigue, illness, or injury. Science and Application of High-Intensity Interval Training is an essential guide for those who want to incorporate HIIT into their own training or their athletes' programming.